Tensile strength of Z-pinned laminates in RTD and hot-wet environment - Li Chenghu; Guo Wei; Wu Zhe (Science and Engineering of Composite Materials, 2017)
Experiments and simulation analysis for tensile strength of Z-pinned laminates were conducted in both room temperature and dry and hot-wet environments. The results of the experiments show that the fracture of [0]6 specimen with Z-pins was longitudinally torn, and there was a row of Z-pins at the fracture of [(±45)/(0,90)]2S specimen with Z-pins. It could be observed that the hot-wet effect on the tensile strength of the Z-pinned laminates increased with percentage of 0-direction fibers decreasing in the laminates from the experiments of the unidirectional tape laminates and the woven cloth laminates. When the volume content of Z-pin increased, the hot-wet effect on tensile strength of Z-pinned [45/0/-45/90]2S laminates with Z-pins would become smaller and smaller. The simulation method of the hot-wet effect on tensile strength of the laminates was combined with the experiment and the finite element analysis. It used 14 nonlinear springs to simulate the longitudinal tearing of [0]6 specimen with Z-pins. The simulation results showed that Z-pin played a role of fulcrum, and because of the lever principle, the fiber bundles were torn at both tips in resin-rich area.